Exploring the Design of Virtual Software for Fire Safety Education in Senior Elementary School Students - Wang, Hsiao-Shen; Tsai, Cheng-I; Liu, Pei-Tsen; Chang, Jia-Yi; Yang, I-Chich (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2024)
Education increasingly recognizes that traditional teaching methods may not sufficiently engage students. This study primarily focuses on the development of the game fire education. This research uses descriptive quantitative methods to describe the development of the Virtual Software for Fire Safety Education game, involving 26 students with experience in game design and testing for initial validation. This preliminary study will guide future experiments involving senior elementary school students, providing foundational insights for further research. Findings highlight game-based learning's capacity to foster engagement and understanding in fire safety education, underscoring its broader application potential.